Análisis de las políticas públicas del Ecuador en materia de comercio exterior con perspectiva en la descarbonización de la movilidad - Tinoco Tello, Lisset Dayanara (2025)
This study analyzes Ecuador's public policies on foreign trade with a focus on the decarbonization of mobility. It examines the regulatory frameworks and international strategies of key actors such as the United States, the European Union, China, and Latin American countries, as well as Ecuadorian regulations that drive the transition toward sustainable electric mobility. Through a multivariable linear regression analysis, the study projects the growth of the electric vehicle market in Ecuador until 2035, considering variables such as vehicle cost, charging infrastructure, driving range, and charging time. The results show that, in an optimistic scenario, sales could reach 32,500 units by 2035, while in a neutral scenario, 7,500 units are expected, and in a pessimistic scenario, 5,289 units. Additionally, the study evaluates the economic feasibility of implementing electric vehicles in Ecuador’s light vehicle fleet by calculating the Total Cost of Ownership (TCO). It compares acquisition, maintenance, and energy consumption costs between electric vehicles and internal combustion vehicles, demonstrating that, in the long term, electric vehicles represent approximately a 20% reduction in operating costs. The research concludes that the adoption of adequate public policies, the expansion of charging infrastructure, and access to economic incentives are key factors in accelerating the transition to sustainable mobility. Furthermore, it highlights the importance of the commitment of the state, industry, and users in transforming Ecuador’s automotive sector toward zero emission mobility.